PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR PADA PERUSAHAAN NON KAPITALISASI BESAR (NON-BIG CAPITALIZATION) DI INDONESIA - Melissa, Anderson (Business Accounting Review, 2015)
Some article stated that non-big capitalization company is not considered by investors and do not become a mayor consideration in investing decision. Because of that, this studies would analyze about the affect of corporate social responsibility (CSR) to investor response on non-big capitalization company in indonesia. The variables that used in this research were CSR as independent variable and investor response that measured by using cummulative abnormal return (CAR) as dependent variable. The other independent variables which were control variable were return on asset (ROA), firm size, debt to equity ratio (DER), and market share. The sample in this research was non-big capitalization company during period of 2008-2012. The data-processing method is done by determining the criterion sample and statistics descriptive analysis that were mean, maximum value, minimum value, and standar deviation. The amount sample that fulfilled the criterion was 216 firm year. Whereas for the analysis-data model was using classical assumption, double linear regression and hypothesis test. The research result showed that the independent variable CSR did not significantly influence CAR. However, control variables that were ROA, firm size, DER, and market share had significantly influence on CAR.